Structural, magnetic and mossbauer spectral studies of nanocrystalline Ni0.5Zn0.5Fe2O4 ferrite powders - Verma, Seema; Joy, Pattayil Alias; Kurian, Sajith (Journal of Alloys and Compounds, 2011)
Nanocrystalline Ni0.5Zn0.5Fe2O4 powders, synthesized by a combustion method are investigated by X-ray diffraction, vibrating sample magnetometry and Mossbauer spectroscopic techniques. We adopt a strategy to systematically control the particle sizes between 4 and 45 nm simply by changing the elemental stoichiometric coefficient, Phi(e), of the combustion mixture. Curie temperature of the superparamagnetic particles of size 4 nm is higher than that of the bulk particles. Interestingly, bigger particles (45 nm) show a comparable room temperature saturation magnetization and exceptionally very high Curie temperature of 833 K, when compared to that of the bulk Ni0.5Zn0.5Fe2O4 material (563 K). (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Chemical synthesis; Magnetisation; Mossbauer spectroscopy; Nanostructured materials